Prevalence and Predictors of Cyberbullying in Middle and High School Students During the COVID-19 Pandemic - Ihsana Sabriani Borualogo; Hedi Wahyudi; Sulisworo Kusdiyati (Jurnal Psikologi, 2023)
Schools were closed during the COVID-19 pandemic, and the learning process has changed dramatically. Students spent countless hours online for learning and leisure activities and risked themselves by engaging in cyberbullying. This study aims are twofold: (1) to investigate the prevalence of cyberbullying perpetration and victimization during the COVID-19 pandemic, and (2) to investigate predictors of cyberbullying perpetration and victimization. A cross-sectional survey method was used in this study. This study used three questionnaires named Cyberbullying Perpetration and Victimization, Problematic Internet Use Questionnaire Short Form (PIUQ-SF-6), and Cyberbullying Attitudes Measure. Participants are middle and high school students (N = 3,752; 52.4% were girls, 81.6% were middle school students). Data were analyzed using descriptive statistics and multivariate linear regression. Results showed that more students engaged in cyberbullying victimization than perpetration. Boys were more likely to engage in cyberbullying perpetration. Girls were more likely to engage in cyberbullying victimization. The most prevalent cyberbullying perpetration and victimization were posted mean or hurtful comments online. PIU, particularly more time spent online, harms both perpetrators and victims, as many as 3.4% for perpetrators and 4.5% for victims. Having fun teasing others online and feeling good attacking others online made the highest contributions to engaging in cyberbullying perpetration, as many as 10.9% and 10.1%, respectively. Do not accept harming others online and do not feel-good attacking others online, protecting the individuals from being cyberbullied as many as 4.2%. The attitude that school rules will be ineffective at stopping cyberbullying made the highest contribution to being cyberbullied, as many as 4.2%.